Optimalisasi Pembelajaran Bahasa Inggris melalui Model Flipped Classroom bagi Siswa Sekolah Menengah Pertama Islam Terpadu (SMP IT) Imam Syafi’i 2 Pekanbaru, Riau - Johari Afrizal; Yulianto Yulianto; Ibnu Hajar; Eldis Febriati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This community service activity was conducted to optimize English language learning through the implementation of the Flipped Classroom model for students of SMP IT Imam Syafi’i 2 Pekanbaru, Riau, Indonesia. The activity aimed to enhance students’ learning engagement, autonomy, and comprehension in English through a student-centered instructional approach. The program was implemented in three stages: preparation, implementation, and evaluation. Learning materials in the form of instructional videos and digital resources were provided prior to classroom meetings to enable students to study independently. Face-to-face sessions were then devoted to interactive discussions, collaborative tasks, and communicative practice to reinforce students’ understanding and language skills. The outcomes of the program indicated increased student participation, improved motivation, and better mastery of English materials. The Flipped Classroom model contributed to creating a more active and meaningful learning environment. Therefore, this community service initiative demonstrates that the Flipped Classroom approach can serve as an effective instructional strategy to support English language learning at the junior high school level